2022
DOI: 10.1530/eje-22-0523
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical thyroid dysfunction and incident diabetes: a systematic review and an individual participant data analysis of prospective cohort studies

Abstract: Objective: Few prospective studies have assessed whether persons with subclinical thyroid dysfunction are more likely to develop diabetes, with conflicting results. We conducted a systematic review of the literature and an individual participant data analysis of multiple prospective cohorts to investigate the association between subclinical thyroid dysfunction and incident diabetes. Methods: We performed a systematic review of the literature in Medline, Embase, and the Cochrane Library from inception to Febru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
1
11
0
1
Order By: Relevance
“…Although it is widely accepted that there is an association between type 1 diabetes and thyroid dysfunction, and consequently guidelines recommend screening individuals with type 1 diabetes for thyroid disorders [ 38 ], the association is less evident for type 2 diabetes. Results from cross-sectional studies and longitudinal studies assessing the risk of diabetes among individuals with thyroid disorders have been inconclusive [ 12 , 19 , 20 , 22 , 39 41 ]. However, very few studies have assessed the association in the inverse direction, i.e., by examining whether individuals with type 2 diabetes are at an increased risk of developing thyroid disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is widely accepted that there is an association between type 1 diabetes and thyroid dysfunction, and consequently guidelines recommend screening individuals with type 1 diabetes for thyroid disorders [ 38 ], the association is less evident for type 2 diabetes. Results from cross-sectional studies and longitudinal studies assessing the risk of diabetes among individuals with thyroid disorders have been inconclusive [ 12 , 19 , 20 , 22 , 39 41 ]. However, very few studies have assessed the association in the inverse direction, i.e., by examining whether individuals with type 2 diabetes are at an increased risk of developing thyroid disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, the temporal relationship between thyroid disorders and MetS remains unclear [ 18 ]. Evidence from longitudinal studies in this field is relatively scarce, and most studies have investigated whether thyroid disorders are prospectively associated with the development of MetS or its components [ 19 22 ]. Interestingly, one study reported evidence of an association between subclinical hypothyroidism and prevalent, but not incident, MetS [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid hormone (TH) controls food intake by regulating appetite and thermogenesis and influences glucose and lipid metabolism and adipogenesis [ 5 ]. MetS, obesity and SHypo are frequent conditions among the adult population and to date, various studies and meta-analyses have been published to assess the relationship between these disorders with controversial results [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Some meta-analyses assessed the relationship between SHypo and MetS, as well as its components.…”
Section: Association Between Subclinical Hypothyroidism and Metabolic...mentioning
confidence: 99%
“…The common causes of subclinical hyperthyroidism include toxic multinodular goiter, toxic adenoma, Graves’ disease, and some exogenous causes ( 4 ). The prevalence of subclinical hyperthyroidism in the general population is 1%–3% ( 5 , 6 ), which varies by age, sex, race, genetic predisposition, iodine status, and the definition of subclinical hyperthyroidism ( 7 ). Women, older individuals, and those living in iodine-deficient regions were more frequent ( 8 ).…”
Section: Introductionmentioning
confidence: 99%